Penggunaan Sabut Kelapa Teraktivasi NaOH sebagai Adsorben Metilen Biru: Utilization of Coconut Fiber NaOH-Activated as Blue Methylene Adsorbent - Anselmus Boy Baunsele; Erly Grizca Boelan; Aloisius Masan Kopon; Maximus M. Taek; Gerardus D. Tukan; Hildegardis Missa (KOVALEN: Jurnal Riset Kimia, 2023)
Methylene blue is a textile dye with carcinogenic and mutagenic properties which can cause various problems for the environment and organisms, therefore it is necessary to treat the waste. This study describes the adsorption of methylene blue using base-activated coconut coir. Coconut coir as waste was prepared into 80 mesh-sized powder and then activated using NaOH solution. The base-activated coconut fiber was then used for methylene blue adsorption under several optimization conditions such as pH, contact time, concentration, and adsorption isotherm. The determination of methylene blue was adsorbed by the adsorbent measured using UV-VIS. The pH and contact time results were 7 and 75 minutes, respectively, with the adsorption capacity (qe) of 1.98 mg g-1 and 99.91%. The isotherm adsorption of blue methylene followed the Langmuir isotherm model with the maximum adsorption capacity (Qmax) of 0.2 mg -1. The result showed that the coconut fiber base activated could be used as a dye adsorbent.